2022
DOI: 10.1002/cjoc.202200502
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Combination of Biodegradable Peptide Polymer and Curcumin as Promising Antibiotic Substitution in Aquaculture to Alleviate the Global Challenge of Antimicrobial Resistance

Abstract: Comprehensive Summary The massive use of antibiotics in aquaculture and resulted antibacterial resistance problem urgently need antibiotic substitutions. Herein, we report a promising substitution of aquaculture antibiotics using a synergistic combination of biodegradable peptide polymers and curcumin, a natural compound from plant. The synergistic combination shows strong antibacterial activity against V. fluvialis and some other common bacteria in aquaculture. The membrane‐damaging antibacterial mechanism ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…The Zeta potential assay was conducted according to previous literature with little modifications. [ 43 ] Staphylococcus aureus USA300 (MRSA) cultured overnight was diluted with phosphate buffer saline (PBS) to 2 × 10 7 CFU/mL. 500 μL of bacteria suspension was merged with an equal volume of curcumin, PLL 20 ‐ b ‐PBLG 20 and their combination to a final concentration of curcumin (50 μg/mL) and PLL 20 ‐ b ‐PBLG 20 (12.5 μg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…The Zeta potential assay was conducted according to previous literature with little modifications. [ 43 ] Staphylococcus aureus USA300 (MRSA) cultured overnight was diluted with phosphate buffer saline (PBS) to 2 × 10 7 CFU/mL. 500 μL of bacteria suspension was merged with an equal volume of curcumin, PLL 20 ‐ b ‐PBLG 20 and their combination to a final concentration of curcumin (50 μg/mL) and PLL 20 ‐ b ‐PBLG 20 (12.5 μg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…In 2022, Liu et al reported a promising substitution of aquaculture antibiotics using a synergistic combination of poly(L-Lys) 80 -r-poly(L-Ser) 20 and curcumin. 50 The synergistic combination showed strong antibacterial activity against V. f luvialis and some other common bacteria in aquaculture. The antimicrobial combination exhibited remarkable bactericidal properties against V. fluvialis, S. agalactiae, and V. cholerae as a synergistic combination.…”
Section: Amp-mimetic Antimicrobial Polymers and Their Involved Synerg...mentioning
confidence: 99%
“…As polypeptides share a similar backbone with peptides and mimic their complexity, functionality, and performance, they have promising potential as biomimetic antimicrobials. In 2022, Liu et al reported a promising substitution of aquaculture antibiotics using a synergistic combination of poly( l -Lys) 80 - r -poly( l -Ser) 20 and curcumin . The synergistic combination showed strong antibacterial activity against V. fluvialis and some other common bacteria in aquaculture.…”
Section: Amp-mimetic Antimicrobial Polymers and Their Involved Synerg...mentioning
confidence: 99%
“…One is to avoid the resistance mechanism of drug‐resistant bacteria and develop antimicrobial agents with new antibacterial mechanisms, [13] such as cationic polymers, [14] antimicrobial peptides, [15] and nanomaterials [16] in antibacterial applications. Another way is to combine antibiotics with non‐antibiotics to reverse the resistance of drug‐resistant bacteria, so that drug‐resistant bacteria can regain their sensitivity to traditional antibiotics [17–19] …”
Section: Introductionmentioning
confidence: 99%
“…Another way is to combine antibiotics with non-antibiotics to reverse the resistance of drug-resistant bacteria, so that drug-resistant bacteria can regain their sensitivity to traditional antibiotics. [17][18][19] Recently, we isolated a new glucolipid compound (1) (Figure 1) from the fermented extract of the Antarctic-sourced fungus Pseudogymnoascus sp. OUCMDZ-4032.…”
Section: Introductionmentioning
confidence: 99%